Synthesis, structure and properties of an octahedral dinuclear-based Cu12 nanocage of trimesoyltri(l-alanine). Issue 12 (25th January 2016) - Chen, Zilu; Liu, Xianlin; Wu, Anfu; Liang, Yuning; Wang, Xinyu; Liang, Fupei
Abstract : We report here a Mo6 C18 4+ -like dinuclear-based octahedral nanocage, presenting antiferromagnetic interactions between the Cu(ii ) ions and nice selectivity on gas adsorption. Abstract : The reaction of a three-armed ligand of trimesoyltri(l -alanine) (TMTAH3 ) with CuCl2 gave [Cu12 (TMTA)8 (H2 O)12 ]·8CH3 CH2 OH·40H2 O (1 ) as expected. It features paddlewheel dinuclear secondary building blocks, six of which are connected by eight TMTA 3− linkers, forming a Mo6 C18 4+ -like dinuclear-based octahedral nanocage. The magnetic studies revealed the presence of antiferromagnetic interactions between the Cu(ii ) ions in1 . The desolvated sample of1 presents nice selectivity on the adsorption of H2 and CO2 over CH4 .